Crip Time Travels Through the Membrane and Vortex : An Autoethnographic Inquiry of Neurodivergent Student Temporality in Higher Art Education - Smith, Timothy J. (Wiley, 2024)
Crip time is a fluid term with various definitions that pertain to the ways that disabled people experience time. In one sense, the effects of crip time can be constraining, particularly when it results in an encounter with ableist institutional and societal barriers. But crip time can also take on a liberatory form as a mode of resistance and a catalyst for structural change. This autoethnographic inquiry explores these various manifestations of crip time and will take form as a kind of crip time travel endeavour that recounts my experiences of temporality as a neurodivergent university art student. Framed through the mental imagery of the membrane and the vortex, I discuss the ways in which my neurodivergent student temporality collided and conflicted with the rigid temporal frameworks of neoliberal higher art education (HAE). I particularly focus on how HAE segments its programming into academic and artistic curricular time. I detail my difficulties keeping up with the academic curricular time to such an extent that the studio time and community time of artistic curricular time became lost or displaced time. Based on this crip time travel inquiry, I will acknowledge and move beyond a confining conception of crip time to offer insights into the liberatory potential of crip time towards reimagining temporal relations, reconceiving student success and opening time for neurodivergent students for critical making and thinking among a community of artist peers and mentors in HAE
Keywords: taidekasvatus; korkea-asteen koulutus; taide; opiskelijat; taiteellinen työ; kokemukset; temporaalisuus; ajankäyttö; autoetnografia; neuromoninaisuus